2020
DOI: 10.1108/jfmm-10-2019-0243
|View full text |Cite
|
Sign up to set email alerts
|

Building apparel manufacturing competitiveness through policy–a system dynamics approach

Abstract: PurposeThe purpose of this paper is to examine the role of Government via its industrial policy aimed at building competitiveness in apparel manufacturing in a developing country.Design/methodology/approachA conceptual framework that proposes the causal relationships between policies and competitiveness is applied to the apparel manufacturing sector in Trinidad and Tobago. The study utilises primary data from interviews and observations, and secondary data sources inclusive of industry and fashion companies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…But, local fashion brands are also enjoying increasing popularity and lucrative market opportunities. The surge in demand for domestic fashion brands is being encouraged by local government authorities, who see the fashion industry as an integral part of the national development strategy (Wilson, 2020). Local fashion brands can benefit from a series of home-based advantages, including easy access to the local market, convenience, customization and cultural connections.…”
Section: Introductionmentioning
confidence: 99%
“…But, local fashion brands are also enjoying increasing popularity and lucrative market opportunities. The surge in demand for domestic fashion brands is being encouraged by local government authorities, who see the fashion industry as an integral part of the national development strategy (Wilson, 2020). Local fashion brands can benefit from a series of home-based advantages, including easy access to the local market, convenience, customization and cultural connections.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson [83] examined the role that the government can play, through its industrial policy, in enhancing competitiveness in apparel manufacturing in Trinidad and Tobago. Using SDM and simulation to analyze data for vertical policies, the study found that three interrelated elements affected apparel manufacturing: the market, apparel products, and productive resources [99].…”
Section: System Dynamics Modeling For Supply Chain Management In Appa...mentioning
confidence: 99%
“…[1][2][3] In the garment manufacturing industry, for instance, largescale machine production has replaced manual production, which has greatly increased output and reduced manufacturing costs, but at the same time has created overproduction. 4 Only garment customization can solve the production capacity, achieve zero inventory, guide accurate consumption and realize accurate manufacturing. 5 The growing commercial value of garment design, manufacturing and sales have driven the rapid development of anthropometric and mannequin reconstruction technologies.…”
mentioning
confidence: 99%